Democratic development states in Southern Africa : a study of Botswana and South Africa - Nagar, Marcel Felicity (Department of Political Studies, 2016)
In light of the growing consensus surrounding the need for the emergence of Democratic Developmental States in Africa, this thesis analyses the concept within the context of two Southern African states: Botswana and South Africa. In this regard, it critically analyses the extent to which Botswana and South Africa can be considered to be Democratic Developmental States by making use five benchmarks of a Democratic Developmental State. It does so by firstly exploring and defining the concept and theory of the Developmental State as well as the concept of the Democratic Developmental State. Secondly, the thesis surveys the contributions made by five key authors, namely, Richard Sklar, Adrian Leftwich, Mark Robinson, Gordon White and Omano Edigheji, to the topic of the Democratic Developmental State and outlines the following five benchmarks of a Democratic Developmental State: Development-Oriented Political Leadership; Effective and Well-Insulated Economic Bureaucracy; Developmental Success; Consolidated Electoral Democracy; and Popular Participation in the Development and Governance Process. Thirdly, the five benchmarks are used to critically analyse whether Botswana and South Africa can truly be regarded as Democratic Developmental States. In this regard, the thesis finds that neither state fully exhibits all five outlined benchmarks of a Democratic Developmental State: While Botswana exemplifies most of the five outlined benchmarks of a Democratic Developmental State, this thesis finds that South Africa still has a long to go before it can be regarded as a Democratic Developmental State. In this manner, this thesis provides possible recommendations which will assist both Botswana and South Africa towards becoming fully-fledged Democratic Developmental States.